Growth Stages and Inter-Species Gut Microbiota Composition and Function in Captive Red Deer (Cervus elaphus alxaicus) and Blue Sheep (Pseudois nayaur) - Yao Zhao; Jia Sun; Mengqi Ding; Romaan Hayat Khattak; Liwei Teng; Zhensheng Liu (Animals, 2023)
Blue sheep and red deer, second-class key protected animals in China, are sympatric species with a high degree of overlap of food resources in the Helan Mountains, China. Previous studies with blue sheep and red deer in nature have shown that their physiology is closely related to their gut microbiota. However, growth stages and changes occurring in these species in captivity are still unknown. Thus, 16S rRNA gene sequencing was used to explore diversity, composition and function of the gut microbiota in these two animal species. The diversity and structure of the gut microbiota in captive blue sheep and red deer changed at different growth stages, but the dominant microbiota phyla in the gut microbiota remained stable, which was composed of the phyla Firmicutes, Bacteroidetes and Verrucomicrobia. Moreover, gut microbiota diversity in juvenile blue sheep and red deer was low, with the potential for further colonization. Functional predictions showed differences such as red deer transcription being enriched in adults, and blue sheep adults having a higher cell wall/membrane/envelope biogenesis than juveniles. Microbial changes between blue sheep and red deer at different growth stages and between species mainly depend on the abundance of the microbiota, rather than the increase and absence of the bacterial taxa.